Wastewater treatment modelling with smoothed particle hydrodynamics. (January 2016) - Meister, Michael; Rauch, Wolfgang
Abstract: In this paper a novel hydrodynamic wastewater treatment (WWT) model based on smoothed particle hydrodynamics (SPH) is presented. The hydraulics of the wastewater treatment plant is modelled in detail with SPH. The SPH solver is coupled to the activated sludge model such that the influence on biokinetic processes is described. The key innovation of the present WWT model is that both the biokinetics and the wastewater hydraulics are simultaneously solved for non-steady flows. After validating the present method against the software ASIM 5, the capabilities are demonstrated for a full-scale treatment plant simulation. We investigate the stirrer and aeration induced mixing within the reactor compartments as well as the resulting concentrations of the biokinetic compounds. Following the establishment of a local coupling between the hydraulics and the biokinetics, the biokinetic concentrations within a treatment plant can be spatially resolved with a high resolution. Highlights: Novel wastewater treatment model based on smoothed particle hydrodynamics (SPH). CFD method coupled to biokinetic model which is applicable to unsteady flows. Simultaneous simulation of wastewater hydraulics and biokinetics. First-ever application of SPH in wastewater treatment. Release of self-developed software SPHASE .